If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -1p = 3 Solving 4 + -1p = 3 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1p = 3 + -4 Combine like terms: 4 + -4 = 0 0 + -1p = 3 + -4 -1p = 3 + -4 Combine like terms: 3 + -4 = -1 -1p = -1 Divide each side by '-1'. p = 1 Simplifying p = 1
| 9=-4-m | | 25+.02x=10+.05x | | -1/4(0)-2 | | 2.2=1.2(-1.16)+-3.8 | | 13=5.2 | | -(8y+1)-(-7y-2)=0 | | sin(8x)=1 | | 4/9Y-1.4 | | 6x-2=6(X-7) | | 3+4(1+5)=31 | | 180(3-2)=s | | 5(x+1.67)=4x | | 202=1.2(-1.16)-3.8 | | 4(-9+x)=-24 | | 1/5(1)-2(-5)=1 | | -6-4=4x+4-3x | | 6[6-(-5x-3)]=270x+198 | | -4+x=-4 | | 1/5(5)-2(-1)=5 | | -1/3+(-1/2) | | 2x+36=3+8x-9 | | log(4k-5)=log(2k-1) | | -1/4(4)-2 | | 4/6x=2/9 | | -6-4=4x+4-3c | | 5(-4x+8)=-180 | | x+.75= | | 22/5p=10 | | 4=22+b/9 | | -1/5=37/5+2 | | -1/3+7/8 | | 4x+14=2x+10 |